Pharmacokinetics, Pharmacodynamics, and Pharmacogenetics of Efavirenz 400 mg Once Daily During Pregnancy and Post-Partum. (23rd February 2018) - Lamorde, Mohammed; Wang, Xinzhu; Neary, Megan; Bisdomini, Elisa; Nakalema, Shadia; Byakika-Kibwika, Pauline; Mukonzo, Jackson K; Khan, Waheed; Owen, Andrew; McClure, Myra; Boffito, Marta
Abstract: Background: A clinical trial showed that efavirenz 400 mg once daily (EFV400) is as effective as the standard adult dose. World Health Organization recommends EFV400 as an alternative first-line agent, but data are lacking in the third trimester of pregnancy (TT). We investigated the pharmacokinetics, efficacy, and CYP2B6 pharmacogenetics in HIV-infected women (WLWH) on EFV400 during TT and post-partum (PP). Methods: An open-label 2-center study (United Kingdom, Uganda) was conducted in WLWH receiving antiretroviral regimens containing efavirenz 600 mg, who had their efavirenz dose reduced to EFV400. Weekly therapeutic drug monitoring (TDM), steady-state pharmacokinetic profiles (TT and PP), safety, virological efficacy, and CYP2B6 polymorphisms at positions 516 (C > T) and 938 (T > C) were evaluated. Results: Twenty-five WLWH of African origin were enrolled. All had viral loads <50 copies/mL at baseline, which were maintained throughout the study. No infant was HIV infected. No WLWH were withdrawn due to low EFV400 TDM results. Geometric mean ratios (TT/PP; 90% confidence interval) for EFV400 maximum observed plasma concentration, area under the curve, and plasma concentration measured 24 hours after the observed dose were 0.97 (.85–1.10), 0.87 (.76–.99), and 0.77 (.65–.91), respectively. Five of 25 WLWH were slow metabolizers. Conclusions: Although EFV400 pharmacokinetic parameters were slightly lower for TT compared with PP values, efavirenz concentrations exceeded cutoff levels established by the study and those measured in antiretroviral-naive patients receiving EFV400 in ENCORE1. All subjects maintained a viral load <50 copies/mL, suggesting that EFV400 can be used in pregnant WLWH. Abstract : We investigated pharmacokinetics for once-daily efavirenz 400 mg in pregnant women with human immunodeficiency virus. Efavirenz concentrations were maintained above those in patients receiving efavirenz 400 mg in the ENCORE1 study, suggesting that this regimen can be used in pregnancy.